2004
DOI: 10.1016/s0002-9440(10)63340-8
|View full text |Cite
|
Sign up to set email alerts
|

Lis1 Is Necessary for Normal Non-Radial Migration of Inhibitory Interneurons

Abstract: Type I lissencephaly is a central nervous system (CNS) malformation characterized by mental retardation and epilepsy. These clinical features suggest a deficit in inhibitory neurons may, in part, underlie the pathogenesis of this disorder. Mutations in, or deletions of, LIS1 are the most commonly recognized genetic anomaly associated with type I lissencephaly. The pathogenesis of type I lissencephaly is believed to be a defect in radial neuronal migration, a process requiring LIS1. In contrast the inhibitory n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
75
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 93 publications
(84 citation statements)
references
References 45 publications
9
75
0
Order By: Relevance
“…The distinction between radial and tangential migration may be blurred somewhat in the RMS, as neurons undergo chain migration but through a substrate of glial guidance. A similar requirement for LIS1 and components of the reelin pathway in both radial and tangential migration have reported 18,[60][61][62] .…”
Section: As a Regulator Of Radial And Tangential Migrationsupporting
confidence: 66%
“…The distinction between radial and tangential migration may be blurred somewhat in the RMS, as neurons undergo chain migration but through a substrate of glial guidance. A similar requirement for LIS1 and components of the reelin pathway in both radial and tangential migration have reported 18,[60][61][62] .…”
Section: As a Regulator Of Radial And Tangential Migrationsupporting
confidence: 66%
“…However, current evidence suggests that many of these mutants display defects in both modes of migration (McManus et al, 2004;Kappeler et al, 2006;this study). Impairment in the migration, disposition, and proper integration of interneurons in the cortical circuitry may explain, at least in part, the epilepsy and mental retardation observed in lissencephaly.…”
Section: Cortical Interneurons In Dclk and DCX Mutant Micementioning
confidence: 84%
“…Specifically, McManus et al (2004) have reported that LIS1-deficient interneurons migrate more slowly than wildtype cells in brain slices prepared from E14.5 Lis1 knock-out mice. The defects in cortical interneuron migration that result from inactivation of DCX or LIS1 resemble the reported impairment in radial migration of pyramidal neurons after DCX RNAi in combination with in utero electroporation in rat embryonic brain (Bai et al, 2003).…”
Section: Interneuron Migration Is Delayed After DCX Rnaimentioning
confidence: 99%
“…Mice heterozygous for a Lis1 null allele display only mild defects in neuronal migration, but further reduction of Lis1 levels by combining a null allele with a hypomorphic Lis1 allele profoundly disrupts cortical lamination (Gambello et al 2003;Hirotsune et al 1998). In many Lis1-deficient neurons, the extension of the leading process is unaffected (but see McManus et al 2004), suggesting that the perturbed neuronal migration most likely results from defects in nucleokinesis (Shu et al 2004;Tanaka et al 2004;Tsai and Gleeson 2005). Lis1 associates with microtubules and a subpopulation of Lis1 localizes to the centrosome.…”
Section: Nucleokinesismentioning
confidence: 99%
“…Although the function of Lis1, DCX, DCLK, and CDK5 in nucleokinesis has been primarily studied in radially migrating cells, analysis of other neuronal populations suggests that they play a universal role in this process (Friocourt et al 2007;Kappeler et al 2006;McManus et al 2004;Nasrallah et al 2006;Rakić et al 2009). …”
Section: Nucleokinesismentioning
confidence: 99%